SOIL-STRUCTURE INTERACTION ANALYSIS OF PILES FOUNDATION OF CIPUTRA WORLD 1 TOWER 4 BUILDING - TANJUNG (NIM: 15010112), CHRISTOPHER
Earthquake has become one of the main considerations in designing infrastructure in many countries for many years. Generally, structure response caused by an earthquake is considered independent from soil response so there is an assumption that there is no interaction between upper structure and soil. However, in reality structural responses are dependent on soil responses and soil responses are dependent on structural response. This dependency between soil and structure responses is called soil-structure interaction or SSI. In conventional structure design, SSI is often neglected to simplify the design criteria. SSI can be neglected for a light structure, like simple warehouse and houses, on relatively stiff soil, but for massive structure like tall building on relatively soft soil, SSI can be the decisive factor in structure design. There are two methods which can be used to evalute SSI, direct analysis and substructure approach. In direct analysis, the upper structure and soil are modeled and analyzed as one system, usually this method is done by using finite element method. In substructure approach, the foundation and upper structure are modeled separately then these models will be combined to formulate the complete solution of the SSI problem. Soil structure interaction consists of inertial interaction and kinematic interaction. Inertial interaction is soil deformation which is caused by inertial forces like base shear and base moment. Kinematic interaction is the structure response which is caused by foundation stiffness which convert the free field motion into foundation input motion. There are two general kinematic interaction which are commonly known, the base slab averaging and embedment effect. In this design, substructure approach is used so that the effect of foundation and sub structure stiffnes in kinematic interaction can be analyzed based on several codes like NEHRP, FEMA, and SNI. In this design, the effect of pile filtering effect is also analyzed based on studies which has been done about soil-structure interaction. In order to calculate the sub structure stiffness, two models are used in this study which are basement structure which consists of three-story structure and pile foundations which consists of thirteen groups of piles. From the result of the analysis, it was shown that because of inersial interaction there is a slight increase of the structure period and because of kinematic interaction there is a slight decrease of spectral acceleration. In pile filtering analysis, there is no spectral acceleration reduction at all. These effects are caused by relatively stiff soil under the foundation and also the stiffness of the pile foundation which is quite high.